2024
DOI: 10.1111/anae.16241
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity, socio‐economic deprivation and postpartum outcomes following caesarean delivery: a multicentre cohort study

J. E. O'Carroll,
L. Zucco,
E. Warwick
et al.

Abstract: SummaryDisparities relating to postpartum recovery outcomes in different socio‐economic and racial ethnic groups are underexplored. We conducted a planned analysis of a large prospective caesarean delivery cohort to explore the relationship between ethnicity, socio‐economic status and postpartum recovery. Eligible patients were enrolled and baseline demographic, obstetric and medical history data were collected 18 h and 30 h following delivery. Patients completed postpartum quality of life and recovery measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In a separate study in Anaesthesia , data from 1000 patients who had a caesarean delivery in England during two weeks in October 2021 showed that white women had a shorter hospital stay (35 hours) compared with Asian (44 hours) and black women (49 hours) 2. And at day 30 Asian women had over twice the risk of moderate or severe pain compared with white women, although there was no difference in the use of pain drugs.…”
Section: Caesarean Deliveriesmentioning
confidence: 99%
“…In a separate study in Anaesthesia , data from 1000 patients who had a caesarean delivery in England during two weeks in October 2021 showed that white women had a shorter hospital stay (35 hours) compared with Asian (44 hours) and black women (49 hours) 2. And at day 30 Asian women had over twice the risk of moderate or severe pain compared with white women, although there was no difference in the use of pain drugs.…”
Section: Caesarean Deliveriesmentioning
confidence: 99%